Peningkatan Kompetensi Guru dalam Melaksanakan Proses KBM melalui Pembinaan Pengawas SD Kecamatan Mendahara Sekolah Binaan pada Semester Ganjil Tahun Ajaran 2021/2022 - Amir Amir (Departement of Mathematics Education, 2023)
This study aims to obtain information and discuss increasing teacher competence in carrying out the teaching and learning process through fostering supervisors of SD Mendahara Subdistrict assisted schools in the odd semester of the 2021/2022 academic year. This type of research is school action research. Research Actions SDN Mendahara District, namely SDN 148/X Sinar Kalimantan in the odd semester of the 2021/2022 academic year with 6 teacher subjects. Data was collected through observation sheets, field notes, and documentation. Data analysis techniques use proportions and data reduction. Implementation of coaching by supervisors that focus on increasing teacher competence in carrying out fun learning has increased. Based on the results of the research, it can be interpreted that through coaching supervisors can improve teacher competence in carrying out the teaching and learning process at SD Mendahara Sub-District target schools in the odd semester of the 2021/2022 school year.